Electronic, Structural, and Optical Properties of Zinc Blende and Wurtzite Cadmium Sulfide (CdS) Using Density Functional Theory - Teshome Gerbaba Edossa; Menberu Mengasha Woldemariam (Advances in Condensed Matter Physics)
Zinc blende (zb) and wurtzite (wz) structure of cadmium sulfide (CdS) are analyzed using density functional theory within local density approximation (LDA), generalized gradient approximation (GGA), Hubbard correction (GGA + U), and hybrid functional approximation (PBE0 or HSE06). To assure the accuracy of calculation, the convergence test of total energy with respect to energy cutoff and k-point sampling is performed. The relaxed atomic position for the CdS in zb and wz structure is obtained by using total energy and force minimization method following the Hellmann–Feynman approach. The structural optimization and electronic band structure properties of CdS are investigated. Analysis of the results shows that LDA and GGA underestimate the bandgap due to their poor approximation of exchange-correlation functional. However, the Hubbard correction to GGA and the hybrid functional approximation give a good bandgap value which is comparable to the experimental result. Moreover, the optical properties such as real and imaginary parts of the dielectric function, the absorption coefficient, and the energy loss function of CdS are determined.